The role of school organizational conditions in teacher psychological resilience and stress during COVID-19 pandemic: A moderated mediation model - Fu, Chunhua; Ouyang, Mingkun; Liu, Xian; Xu, Guilin; Wang, Huimei; Ye, Zhenying; Zhao, Jiajing (Frontiers in Psychology, 2023)
Educational reforms facilitate the relief of teacher stress via enhancing school organizational conditions. However, limited research has explored the effects of school organizational conditions on teacher stress in China. Using a sample of 734 primary and secondary school teachers from 30 provinces or municipalities of China, this study examined the effects of school organizational conditions on teacher stress in China, with a particular focus on the mediating role of psychological resilience as an important psychological condition and moderating role of perceived COVID-19 crisis strength. The results demonstrated that school organizational conditions had significant and negative effects on teacher stress. Psychological resilience significantly mediated the effects of both school organizational conditions and teacher stress. Perceived COVID-19 crisis strength, as a significant moderator, negatively correlates school organizational conditions and psychological resilience and positively correlates teacher stress. Implications have been provided accordingly.